2017
DOI: 10.33736/ijbs.546.2017
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Effects of Value on Service Quality-Satisfaction Relationship in Malaysian Tourism Industry

Abstract: The ways to maintain and increase customer satisfaction are always the concern of business providers because high satisfaction is closely related to the customers’ positive word of mouth, revisit intentions, and loyalty; which are the key for the success of long term businesses in today’s customer-focused industry. For that reason, more satisfaction studies, especially on the elements that contribute to higher satisfaction level are needed. Previous researches discovered several explanatory predictors to satis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 40 publications
2
7
0
Order By: Relevance
“…Clemes et al (2013),Kwok et al (2017), andde Oliveira Silva et al (2020). Finally, the relationship between satisfaction → loyalty (H8) is also corroborated among others byChen et al (2005), Alves and Raposo (2007),Tsuji et al (2007),Clemes et al (2008),Huili and Jing (2012),Clemes et al (2013),Sultana and Momen (2017), andde Oliveira Silva et al (2020).…”
supporting
confidence: 77%
See 2 more Smart Citations
“…Clemes et al (2013),Kwok et al (2017), andde Oliveira Silva et al (2020). Finally, the relationship between satisfaction → loyalty (H8) is also corroborated among others byChen et al (2005), Alves and Raposo (2007),Tsuji et al (2007),Clemes et al (2008),Huili and Jing (2012),Clemes et al (2013),Sultana and Momen (2017), andde Oliveira Silva et al (2020).…”
supporting
confidence: 77%
“…The causal relationship proposed by Hypothesis H2 (perceived quality → loyalty) is also corroborated by the research carried out by Chandra et al ( 2019 ) and Hassan et al ( 2019 ). The relationship between perceived quality → perceived value (H3) is corroborated by LeBlanc and Nguyen ( 1997 ); Alves and Raposo ( 2007 ); Clemes et al ( 2008 , 2013 ); Huili and Jing ( 2012 ); Kwok et al ( 2017 ), and de Oliveira Silva et al ( 2020 ). The relationship between perceived value → satisfaction (H4) is corroborated by LeBlanc and Nguyen ( 1997 ), Alves and Raposo ( 2007 ), Clemes et al ( 2008 ), Huili and Jing ( 2012 ), Clemes et al ( 2013 ), Kwok et al ( 2017 ), and de Oliveira Silva et al ( 2020 ).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Service quality is one of the attributes that offer differentiation and arouse cusutomers' visit intention (Lien & Kao, 2010). Besides that, Kwok, Jusoh and Khalifah (2017) suggested that the service provider are the key element that determines the perceived service quality among the customers. In addition, Hamenda (2018) stressed that service quality should be introduce in the organisation's strategic plan so that it can improve customers' satisfaction which later lead to loyalty.…”
Section: Service Qualitymentioning
confidence: 99%
“…Rapid privatization of higher education in other nations has resulted in low performance. It is widely recognized that the degree to which actual service performance meets the customer's requirements and expectations determines service quality (Kwok et al, 2017). As a result, Malaysia must devise ways to avoid falling into this trap.…”
Section: Educational Tourism In Malaysiamentioning
confidence: 99%